Read and write an unbound world : african poetics of an ecological governance - (:unkn) unknown (My University, 2020)
African novels allows to read and experience different states of unbinding (ecological, social, political) which tear apart our world. These fractures hamper not only interpersonal relationships, spiritualities, ethical systems, but also our connection to the environment. By taking as a corpus a set of works coming mainly from sub-Saharan Africa, this thesis sheds light on these experiences of unbinding represented in contemporary novels. It shows that they can actually be seen as symptoms of deeper ailments ; if regular institutions in charge of governance, whether states or international actors, are able to name and quantify them, they fail to fight them. Our hypothesis is that literature, through the sharing of experiences it brings, is likely to recreate the link where it has been broken. At the fictional scale, narrative and stylistic strategies represent ways of creating links beyond the human sphere alone. This extended community that the novels create is the cornerstone of an ecological governance based on the inclusion of all voices and the recognition of the role played by history and memory. Literature therefore plays an ethical and political role, inviting readers to participate in this movement of putting into common a shared meaning through a new relationality.
Keywords: African Research